7-Ketocholesterol is increased in the plasma of X-ALD patients and induces peroxisomal modifications in microglial cells: Potential roles of 7-ketocholesterol in the pathophysiology of X-ALD. Issue 169 (May 2017) - Nury, Thomas; Zarrouk, Amira; Ragot, Kévin; Debbabi, Meryam; Riedinger, Jean-Marc; Vejux, Anne; Aubourg, Patrick; Lizard, Gérard
Graphical abstract: Highlights: Plasma levels of GSH, α-tocopherol, and docosahexaenoic acid are decreased in X-ALD. 7-Ketocholesterol, 7β- and 7α-hydroxycholesrol, and HODEs are increased in X-ALD. 7-Ketocholesterol induces oxiapoptophagy on BV-2 murine microglial cells. 7-Ketocholesterol induces several peroxisomal modifications on BV-2 cells. Abstract: X-linked adrenoleukodystrophy (X-ALD) is a genetic disorder induced by a mutation in the ABCD1 gene, which causes the accumulation of very long-chain fatty acids in tissue and plasma. Oxidative stress may be a hallmark of X-ALD. In the plasma of X-ALD patients with different forms of the disease, characterized by high levels of C24:0 and C26:0, we observed the presence of oxidative stress revealed by decreased levels of GSH, α-tocopherol, and docosahexaenoic acid (DHA). We showed that oxidative stress caused the oxidation of cholesterol and linoleic acid, leading to the formation of cholesterol oxide derivatives oxidized at C7 (7-ketocholesterol (7KC), 7β-hydroxycholesterol (7β-OHC), and 7α-hydroxycholesrol (7α-OHC)) and of 9- and 13-hydroxyoctadecadienoic acids (9-HODE, 13-HODE), respectively. High levels of 7KC, 7β-OHC, 7α-OHC, 9-HODE and 13-HODE were found. As 7KC induces oxidative stress, inflammation and cell death, which could play key roles in the development of X-ALD, the impact of 7KC on the peroxisomal status was determined in microglial BV-2 cells. Indeed, environmental stress factors such as 7KC could exacerbate peroxisomal dysfunctions in microglial cells and thus determine the progression of the disease. 7KC induces oxiapoptophagy in BV-2 cells: overproduction of H2 O2 and O2 −, presence of cleaved caspase-3 and PARP, nuclear condensation and/or fragmentation; elevated [LC3-II/LC3-I] ratio, increased p62 levels. 7KC also induces several peroxisomal modifications: decreased Abcd1, Abcd2, Abcd3, Acox1 and/or Mfp2 mRNA and protein levels, increased catalase activity and decreased Acox1-activity. However, the Pex14 level was unchanged. It is suggested that high levels of 7KC in X-ALD patients could foster generalized peroxisomal dysfunction in microglial cells, which could in turn intensify brain damage.